Against Meritocracy Culture, power and myths of mobility - Littler, Jo (Routledge, 2017)
In this book Jo Littler argues that meritocracy is the key cultural means of legitimation for contemporary neoliberal culture - and that whilst it promises opportunity, it in fact creates new forms of social division. Against Meritocracy is split into two parts. Part I explores the genealogies of meritocracy within social theory, political discourse and working cultures. It traces the dramatic U-turn in meritocracy's meaning, from socialist slur to a contemporary ideal of how a society should be organised. Part II uses a series of case studies to analyse the cultural pull of popular 'parables of progress', from reality TV to the super-rich and celebrity CEOs, from social media controversies to the rise of the 'mumpreneur'. Paying special attention to the role of gender, 'race' and class, this book provides new conceptualisations of the meaning of meritocracy in contemporary culture and society.
Description based on print version record.
KU Select 2018: HSS Backlist Books
Keywords: Social Science / Media Studies; Social sciences; Electronic books